Volume 4A: Combustion, Fuels and Emissions 2015
DOI: 10.1115/gt2015-42919
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency Route to Combustion Instability in a Laboratory Spray Combustor

Abstract: In the present study, we investigate the phenomenon of transition of a thermoacoustic system involving two-phase flow, from aperiodic oscillations to limit cycle oscillations. Experiments were performed in a laboratory scale model of a spray combustor. A needle spray injector is used to generate a droplet spray having one dimensional velocity field. This simplified design of the injector helps in keeping away the geometric complexities involved in the real spray atomizers. We investigate the stability of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…These intermittent bursts last longer as the point of onset is approached. These intermittent bursts are also reported in other studies (Clavin et al, 1994;Gotoda et al, 2014;Kabiraj et al, 2015a;Huang, 2015;Pawar et al, 2016;Wilhite et al, 2016). Intermittency is often analysed using recurrence plots (figure 11 and supplementary materials), which represent time series data graphically.…”
Section: Intermittencysupporting
confidence: 73%
“…These intermittent bursts last longer as the point of onset is approached. These intermittent bursts are also reported in other studies (Clavin et al, 1994;Gotoda et al, 2014;Kabiraj et al, 2015a;Huang, 2015;Pawar et al, 2016;Wilhite et al, 2016). Intermittency is often analysed using recurrence plots (figure 11 and supplementary materials), which represent time series data graphically.…”
Section: Intermittencysupporting
confidence: 73%
“…11(d) indicates stronger nonlinearity. Such large-amplitude intermittency oscillations are unwanted in propulsion systems, since it may lead to fracture of the brittle material or may cause deformation of the ductile material [48,49]. In general, this study confirms the strong impact of hydrogen on producing and the characteristics of the NH 3 -H 2 -combustion-driven pulsating oscillations.…”
Section: Effect Of Hydrogen Mass Fraction H2supporting
confidence: 73%
“…15. This is based on the well-known Rayleigh criteria [28,30,49]. It states that limit cycle oscillations may be produced when acoustic pressure and unsteady heat release are in phase.…”
Section: Heat Exchangers Impact On Limit Cycle and Nox Emissionmentioning
confidence: 99%
“…lifting the flame) and the subsequent heating or cooling of the burner mouth changing the thermal radiation in such a way that the flame reverts to its original position. The position of the flame was artificially controlled by movement of a mesh in a spray combustor by Pawar et al 134 and they observed a progression from stable operation, through periodic bursts of high intensity at 10 s intervals, to shorter intervals, and finally to limit cycling, as the mesh was moved down the tube.…”
Section: Non-linear Observations In Flamesmentioning
confidence: 99%